Implementasi Talaqqi Digital dalam Pembelajaran Al-Qur'an di Pondok Pesantren Nurul Iman Jambi - Fahrina YustiasariLiriwati; Armizi Armizi; Zulhimma Zulhimma; Zulhammi Zulhammi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
In the era of digital transformation, technology has influenced various aspects of life, including Islamic education, especially in Islamic boarding schools. One of the traditional learning methods that has undergone adaptation is the talaqqi method, namely a method of teaching the Koran that involves direct interaction between teachers and students. Digital-based talaqqi is an innovative solution to face geographical challenges and time constraints, as well as answering the need for more flexible learning. This article aims to explore the implementation of digital talaqqi in Islamic boarding schools, its benefits for teaching the Al-Qur'an, as well as the challenges faced in its implementation. This research was conducted using a field study method at the Nurul Iman Jambi Islamic boarding school which has adopted digital-based talaqqi, involving interviews with teachers, students and Islamic boarding school managers. The research results show that digital talaqqi facilitates access to learning for students outside the Islamic boarding school and increases the flexibility of study time. However, this research also found a number of challenges, such as limited internet access in rural areas, lack of direct interaction between teachers and students, as well as technical obstacles that often hamper the learning process. Overall, digital talaqqi offers great opportunities in improving the quality and accessibility of Al learning -Qur'an in Islamic boarding schools, although efforts are still needed to overcome the various challenges that arise in its implementation. With continued technological development, digital-based talaqqi methods can become an important part of Islamic education in the future.